Sistem Pendukung Keputusan Penentuan Lokasi Toko Terbaik Pada PT. Sumber Alfaria Trijaya Menggunakan Metode Analytical Hierarchy Process - Nurlaeli Waruwu (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2021)
Decision Support System is an interactive computer-based system that helps decision making by utilizing data and models to solve unstructured problems. Basically, DSS is designed to support all stages of decision making, from identifying problems, selecting relevant data, determining the approach used in the decision-making process, to evaluating the selection. AHP is a decision support model developed by Thomas L. Saaty. This decision support model will describe complex multi-factor or multi-criteria problems into a hierarchy, the hierarchy is defined as a representation of a complex problem in a multi-level structure where the first level is the goal, followed by the level of factors, criteria, sub criteria, and so on down to the last level of alternatives. With a hierarchy, a complex problem can be broken down into groups which are then arranged into a hierarchical form so that the problem will appear more structured and systematic. In order to compete with several similar companies, PT. Sumber Alfaria Trijaya must be able to provide optimal service not only for consumers, but also for staff and employees in order to work optimally. To be able to answer these challenges, the technology used must be able to balance the need for it. Because this company is engaged in retail, problems will arise either in the store, in the warehouse or in the system used. With a hierarchy, a complex problem can be broken down into groups which are then arranged into a hierarchical form so that the problem will appear more structured and systematic.